2015
DOI: 10.1007/s11606-015-3338-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Incremental and Aggregate Cost of Missed Workdays in Adults with Diabetes

Abstract: OBJECTIVE: Although the national cost of missed workdays associated with diabetes has been estimated previously, we use the most recent available national data and methodology to update the individual and national estimates for the U.S population. METHODS: We identified 14,429 employed individuals ≥ 18 years of age in 2011 Medical Expenditure Panel Survey (MEPS) data. Diabetes and missed workdays were based on self-report, and cost was based on multiplying the daily wage rate for each individual by the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…For each of the nine outcomes, we constructed a modified two-part model, which has become one of the most widely used methods to model health expenditures because of its ability to account for a point mass of zero expenditures and skewed, heteroskedastic expenditures greater than zero. [21][22][23][24][25][26][27] The first part of the model estimates the probability of any expenditure in the overall sample using a logistic regression model adjusting for covariates. Conditional on a positive value, the second part of the model is estimated using a generalized linear model with a gamma distribution and a loglink function to estimate the amount of expenditure increase in the sample with expenditure greater than zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of the nine outcomes, we constructed a modified two-part model, which has become one of the most widely used methods to model health expenditures because of its ability to account for a point mass of zero expenditures and skewed, heteroskedastic expenditures greater than zero. [21][22][23][24][25][26][27] The first part of the model estimates the probability of any expenditure in the overall sample using a logistic regression model adjusting for covariates. Conditional on a positive value, the second part of the model is estimated using a generalized linear model with a gamma distribution and a loglink function to estimate the amount of expenditure increase in the sample with expenditure greater than zero.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional on a positive value, the second part of the model is estimated using a generalized linear model with a gamma distribution and a loglink function to estimate the amount of expenditure increase in the sample with expenditure greater than zero. 25,26 Based on the modified Park Test recommended by Manning and Mullahy 28 and Buntin and Zaslavsky, 29 a gamma distribution with a log link was the best-fitting generalized linear model. To calculate incremental effects of injuries and their SEs from the combined first and second parts of the model, the "margins" function in STATA 14 was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that socio demographic and binary indicators of disease are important covariates that affect medical expenditures 15 and that binary indicators of disease are more effective in accounting for disease burden. 1618 Covariates are age, sex, race/ethnicity, marital status, educational level, health insurance, metropolitan statistical area (MSA), region, poverty/income ratio (income level), calendar year, and comorbidities – diabetes, hypertension, cardiovascular diseases (CVD), emphysema, joint pain, arthritis and asthma. Binary indicators of comorbidities were based on self- report of a positive response to the question, “Have you ever been diagnosed with diabetes, hypertension, stroke, emphysema, joint pain, arthritis, or asthma?” Cardiovascular disease (CVD) was defined by a positive response to a question, “Have you ever been diagnosed with coronary heart disease, angina, myocardial infarction, or other heart diseases?”…”
Section: Methodsmentioning
confidence: 99%
“…T he study by Bishu et al 1 estimated the cost of missed workdays associated with diabetes among individuals aged 18 years or above using nationally representative 2011 Medical Expenditure Panel Survey (MEPS) data. The authors found that having diabetes was associated with 0.84 more of the number of missed work days, as well as with higher costs of missed work days, compared to those without diabetes; individuals with diabetes had $120 higher cost of missed workdays annually.…”
mentioning
confidence: 99%